Long Run Consequences of a Capital Market Union in the European Union - Thomas Davoine (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Capital markets are increasingly integrated, but remain partially separated. To speed up integration, help absorb asymmetric shocks and reduce the need for government support in times of crises, proposals have been put forward to create a Capital Market Union in the EU. This policy brief discusses the long-run consequences of perfectly integrated capital markets, ignoring crises but taking population aging into account. Recent research shows that redistribution would take place, from fast aging to slow aging countries, because investors seek access to the largest labour markets, delivering higher returns on investments. GDP per capita could be over 2% lower in some countries and 2% higher in other countries, compared to autarky. The redistribution pattern depends on social security reforms: some countries would stand to lose from capital market integration without any reforms, but would gain if the retirement age was increased.
Keywords: 330